Ampullary Mixed Adenoneuroendocrine Carcinoma: Surprise Histology, Familiar Management. (October 2017) - Mahansaria, Shyam Sunder; Agrawal, Nikhil; Arora, Asit; Bihari, Chhagan; Appukuttan, Murali; Chattopadhyay, Tushar Kanti
Introduction . Mixed adenoneuroendocrine carcinoma (MANEC) has recently been defined by the World Health Organization in 2010. These are rare tumors and MANECs of ampullary region are even rarer. Only 19 cases have been reported in literature. We present 3 cases; the largest series, second case of amphicrine tumor and first case associated with chronic pancreatitis. Methods . Retrospective review of 3 patients who were diagnosed to have ampullary MANEC. Results . All 3 patients were diagnosed preoperatively as neuroendocrine carcinoma and underwent margin negative pancreaticoduodenectomy. The histopathology revealed MANECs of small cell, mixed type in 2 patients and large cell, amphicrine type in 1 patient. The neuroendocrine component was grade 3 in all, the tumor was T3 in 2 and T2 in 1 and all had nodal metastases. Two patients received adjuvant chemotherapy and 2 of them had recurrence at 13 and 16 months. The median survival was 15 months. Conclusion . Ampullary MANECs are rare tumors. They are diagnosed on histopathologic examination of the resected specimen. Clinical presentation, management, and prognosis is similar to ampullary adenocarcinoma in literature.